PM/sup 2/P: a tool for performance monitoring of message passing applications in COTS PC clusters - Haridasan, M.; Pfitscher, G. H. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
The use of clusters of computers as an environment for high performance computing has been shown to be promising. However, the efficient use of such systems still requires advances that make the application development process be simpler and more productive. The development of cluster monitoring tools is essential to achieve this advances. We present PM/sup 2/P, a tool for use in clusters of personal computers that provides a graphic visualization of the temporal execution of distributed applications that use the MPI standard for message passing. The tool uses an approach involving the parallel port to read the time of events that occur in all different machines of a cluster. It also simulates the execution of task precedence graphs and allocates tasks of a graph to the machines of a cluster, among other functionalities.